1999
DOI: 10.1557/jmr.1999.0533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nanocrystalline titania powder via aerosol pyrolysis of titanium tetrabutoxide

Abstract: Nanocrystalline titanium dioxide was prepared via aerosol pyrolysis of titanium alkoxide precursor at 200-580°C in air and in nitrogen atmospheres. Powders were characterized by x-ray diffraction, thermogravimetric analysis, Brunauer-EmmettTeller analysis, scanning electron microscopy, transmission electron microscopy, energy dispersive spectroscopy, x-ray fluorescence, Raman and infrared spectroscopy, and Berner-type low-pressure impactor. The anatase phase transition was initiated at 500°C in nitrogen and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
(48 reference statements)
2
35
0
Order By: Relevance
“…Experimentally, the critical size of the anatase-to-rutile phase transformation has been reported in the range of 14 ~ 50 nm [11][12], as the size was found to depend on parameters such as temperature [13], impurities [14], and reaction atmosphere [15]. Our experiments indicate that the doping SnO 2 accelerate the anatase-to-rutil phase transformation process via the substitution of Sn 4+ for Ti 4+ .…”
Section: Resultssupporting
confidence: 53%
“…Experimentally, the critical size of the anatase-to-rutile phase transformation has been reported in the range of 14 ~ 50 nm [11][12], as the size was found to depend on parameters such as temperature [13], impurities [14], and reaction atmosphere [15]. Our experiments indicate that the doping SnO 2 accelerate the anatase-to-rutil phase transformation process via the substitution of Sn 4+ for Ti 4+ .…”
Section: Resultssupporting
confidence: 53%
“…The anatase-rutile transformation depends on impurities, grain size, reaction atmosphere, and synthesis conditions (26)(27)(28)(29)(30)(31). Zhang and Banfield (26) reported that the anatase-rutile phase transformation occurred at higher temperature with the addition of Al 2 O 3 .…”
Section: General Implications Of Surface Enthalpies and Enthalpies Ofmentioning
confidence: 99%
“…Zhang et al 4 measured microRaman spectra of nanosized TiO 2 powder prepared by vapor hydrolysis. Ahonen et al 5 observed that anatase synthesized in air transformed to rutile at 973 K, whereas anatase synthesized in nitrogen persisted up to 1173 K, and phase transformation is also affected by the interface nucleation and the presence of impurities. [6][7][8] Wang et al 9 and Nakade et al 10 synthesized rutile and anatase TiO 2 by chemical solution method, and Wu et al 11 did sol-hydrothermal synthesis to produce nanoparticles of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%